Notaries Role Analysis in Implementation of Credit Agreements & Defaults Settlement with Guaranteed Liability - Octantina Widiyastuti; Amin Purnawan; Siti Ummu Adillah (Sultan Agung Notary Law Review, 2021)
Analysis of the Role of a Notary in the Implementation of Credit Agreements and Efforts to Settle Default with Guaranteed Mortgage at Bank BRI, Tegal City requires the assistance of a Notary. This happens because the Notary is authorized to make a form of authentic deed that is able to provide legal protection to the parties to the agreement. Regarding the authority of a Notary as a general official making an authentic deed, it can be seen in the provisions of Article 15 paragraph (1) of Act No.: 30 of 2004 concerning the Position of a Notary. The objectives of this journal research are one, to identify and analyze the role of a Notary in a credit agreement with mortgage guarantees at Bank BRI Tegal City Branch Office; two, to find out and analyze the factors causing the occurrence of Default in the credit agreement with the guarantee of Mortgage at Bank BRI Tegal City Branch Office; three, to find out and analyze how to settle defaults in credit agreements with mortgage guarantees at Bank BRI Tegal City Branch Office. The approach method used is the sociological juridical method, the research specifications used are analytical descriptive, using observation and interviews, secondary data collection techniques using library research, and data analysis methods using qualitative analysis. The results of the research and discussion, First, the role of the Notary in the implementation of the credit agreement, as an official authorized to make an authentic deed who is burdened with responsibility in connection with his work in making the deed and the deed can provide legal certainty for the parties in the credit agreement so that the Notary is to prioritize the balance between the namely rights and obligations of the parties who appear before the Notary. Second, the factors causing the occurrence of Default in the credit agreement with guaranteed mortgage rights at Bank BRI Tegal City Branch Office, there are internal factors and external factors causing non-performing loans. Third, Settlement of default in the credit agreement with collateral rights at the BRI bank Tegal City Branch Office can be done by using rescheduling, reconditioning, and restructuring methods.